Study of the Nanostructure Effect on Polyalkylthiophene Derivatives Films Using Impedance Spectroscopy - Lima Citolino, Lucas Vinicius de [UNESP]; Braunger, Maria Luisa [UNESP]; Rodrigues Oliveira, Vinicius Jesse [UNESP]; Olivati, Clarissa A. [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2017)
In this paper, devices fabricated with a diode-like structure (electrode/polymer/electrode) from spin-coated and nanostructured (Langmuir-Schaefer) films of polythiophene derivatives were characterized by impedance spectroscopy and studied by theoretical fitting to reach a better understanding of the physical processes in the devices. The materials used for this research were the polyalkylthiophene (P3AT) derivatives poly(3-butylthiophene) (P3BT), poly(3-hexylthiophene) (P3HT), poly(3-octylthiophene) (P3OT) and poly(3-decylthiophene) (P3DT). Electrical measurements were performed from 1 Hz to 1 MHz (100 mV ac) while increasing the dc bias in the range from 0 to 2.5 V. The fittings of the experimental results were performed using equivalent circuits. By plotting the theoretical and experimental spectra on a single graph, it was possible to obtain information related to the film morphology, interfacial effects, resistance, capacitance and conductivity of the polymer, thereby enhancing the understanding of this particular type of device. Among the P3AT films, those grown by the Langmuir-Schaefer technique showed higher electrical conductivity, with the only exception being that of P3BT.
Keywords: polythiophene; nanostructured film; impedance spectroscopy